2010
DOI: 10.1194/jlr.m001859
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of cholesterol in microdissected Alzheimer’s disease senile plaques as assessed by mass spectrometry

Abstract: The core of the SP is made of aggregated amyloid-␤ (A ␤ ) peptide. A ␤ peptide is cleaved from a type 1 transmembrane protein, the amyloid protein precursor (APP), by the sequential activities of the ␤ and ␥ secretases. Special staining of microscopic sections from brain samples of AD patients has long suggested that SPs were enriched in lipids ( 5 ). The presence of cholesterol among those lipids is plausible since apolipoprotein E (apoE), a transporter of cholesterol, has been found in the SPs by immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 29 publications
1
71
0
Order By: Relevance
“…This would suggest that cholesterol itself would be a potent activator of fibril formation. Indeed, the role of cholesterol in Alzheimer disease has garnered great attention in the literature, and there are several studies that indicate that cholesterol can modulate amyloid fibril formation and may be important in the pathogenesis of Alzheimer disease (31)(32)(33)(34)(35)(36)(37). The activation by several sterol-containing molecules suggests that there is a specific sterol binding site that enhances aggregation.…”
Section: Tablementioning
confidence: 99%
“…This would suggest that cholesterol itself would be a potent activator of fibril formation. Indeed, the role of cholesterol in Alzheimer disease has garnered great attention in the literature, and there are several studies that indicate that cholesterol can modulate amyloid fibril formation and may be important in the pathogenesis of Alzheimer disease (31)(32)(33)(34)(35)(36)(37). The activation by several sterol-containing molecules suggests that there is a specific sterol binding site that enhances aggregation.…”
Section: Tablementioning
confidence: 99%
“…The authors have postulated that these genetic variations in ABCA1 and NPC1 genes could act in concert and that the underexpression of NPC1 together with the underexpression of ABCA1 could result in increased cholesterol accumulation and increased AD risk. Indeed, increased cholesterol levels in AD brains were recently reported (Lazar et al, 2013;Panchal et al, 2010) and epidemiological studies have confirmed midlife high serum cholesterol levels as a risk factor for AD (Pappolla et al, 2003).…”
Section: Npc1 Genetic Variations In Alzheimer's Diseasementioning
confidence: 99%
“…Cholesterol and other members of the sterol family play an important role in membrane structure and fluidity and are involved in various diseases such as atherosclerosis [39] and Alzheimer's disease [40]. Their analysis is complicated by poor ionization yields in ESI and by the structural diversity due to numerous isomers.…”
Section: Sterols and Oxysterolsmentioning
confidence: 99%